2018
DOI: 10.7759/cureus.3265
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Beta-thalassemia Mutations in Couples Referred for Chorionic Villus Sampling at Bahawal Victoria Hospital, Bahawalpur

Abstract: IntroductionThe prevalence of beta-thalassemia mutations is different in various castes, regions, and ethnic groups. By knowing this prevalence, we can conduct a targeted screening of only the high-risk population and only for the specific mutations that are prevalent in each group.ObjectiveThe purpose of this study was to determine the regional, caste-wise, and ethnic spectrum of beta-thalassemia mutations in couples referred for a prenatal diagnosis.MethodsA cross-sectional analytical study was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…There was no significant difference between the results of our study and this study. 16 The study conducted by Kanwal et al in 2017 showed that IVS1-5, Fr8-9 and Fr41-42 were the prevailing mutations and uncommon mutations were Del 619, IVS1-1, Cd15 and Cd16. There was some difference in the results of our study and this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference between the results of our study and this study. 16 The study conducted by Kanwal et al in 2017 showed that IVS1-5, Fr8-9 and Fr41-42 were the prevailing mutations and uncommon mutations were Del 619, IVS1-1, Cd15 and Cd16. There was some difference in the results of our study and this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other less common mutations were Fr 41-42, Fr 16, IVS1-1 and Cap+1. A study by Zafar et al 2018 showed that the most common mutations were Fr 8-9, IVS 1-5, Cd5, Fr41-42 and Del 619. There was no significant difference between the results of our study and this study.…”
Section: Discussionmentioning
confidence: 99%
“…Tis is typically confrmed through additional testing, such as hemoglobin electrophoresis or genetic testing, to defnitively diagnose beta-thalassemia trait. It is important to note that interpretation of HbA 2 levels should be done in conjunction with clinical fndings and other laboratory tests for a comprehensive diagnosis [23][24][25][26].…”
Section: Iron-defciency Anemia or Talassemia Carrier?mentioning
confidence: 99%